Making Young Voters: The Impact of Preregistration on Youth Turnout. Issue 2 (3rd March 2015) - Holbein, John B.; Hillygus, D. Sunshine
Abstract : Recent research has cast doubt on the potential for various electoral reforms to increase voter turnout. In this article, we examine the effectiveness of preregistration laws, which allow young citizens to register before being eligible to vote. We use two empirical approaches to evaluate the impact of preregistration on youth turnout. First, we implement difference‐in‐difference and lag models to bracket the causal effect of preregistration implementation using the 2000–2012 Current Population Survey. Second, focusing on the state of Florida, we leverage a discontinuity based on date of birth to estimate the effect of increased preregistration exposure on the turnout of young registrants. In both approaches, we find preregistration increases voter turnout, with equal effectiveness for various subgroups in the electorate. More broadly, observed patterns suggest that campaign context and supporting institutions may help to determine when and if electoral reforms are effective.